Building capacity in neurodevelopment assessment of children in sub-Saharan Africa: A quality assurance model to implement standardized neurodevelopment testing. Issue 4 (19th May 2019) - Ruiseñor-Escudero, Horacio; Familiar, Itziar; Nyakato, Mary; Kutessa, Agatha; Namukooli, Jackie; Ssesanga, Titus; Joyce, Celeste; Laughton, Barbara; Grab, Janet; Chernoff, Miriam; Vhembo, Tichaona; Fairlie, Lee; et al.
ABSTRACT: Compromised neurodevelopment (ND) among infants and children is prevalent in sub-Saharan Africa. Standardized testing of ND is frequently prohibitive in these contexts, as tests require skilled staff for their application. In this paper, we present a quality assurance (QA) model (QualiND) for standardized ND testing, discussing findings and implications from our experience applying the Kaufman Assessment Battery for Children second edition (KABC-II). The QualiND model was implemented within IMPAACT P1104s study, a multisite, prospective study including 615 children affected by HIV. From 2014 to 2016, the QualiND managed 18 testers across 6 sites located in 4 African countries applying the KABC-II in 9 local languages. The QualiND is a multilevel, video-assisted iterative model incorporating remote evaluation, feedback, and supervision roles. Using an ad hoc rubric, videos of test application were evaluated by experienced staff in a centralized QA center. At each study site, testers and supervisors reviewed feedback from videos received via email from the QA center and devised an action plan to address testing errors and deficiencies. There were few instances of invalid tests and few barriers to test completion. Over 97% of KABC-II tests across sites were considered to be valid by the QA center. Overall, the QualiND model was a useful platform for remote supervision to nonspecialist and minimally trained research staff. The QualiND model may be useful to researchers and organizations involved in measuring early child development using standardized tests in low and middle-income countries.